The Use of Google Form Application as Students Worksheet in Reading Descriptive Text at The Seventh Grade of SMP Muhammadiyah 3 Medan - Khusnul Khotimah Nadeak; Rika Rika (REGISTER: Journal of English Language Teaching of FBS-Unimed, 2022)
The objective of this study are to identify the purposes of using Google Form by the teachers, and to investigate how google form is used by the teachers at the the seventh grade of SMP Muhammadiyah 3 Medan. To achieve these purposes the researcher used qualitative research design. The subjects of the study are two teachers of English of SMP Muhammadiyah 3 Medan. Techniques of data collection were observation and interview The findings show that purposes of using google form are : to save more time in doing quiz questions, to saves paper, to make learning process easier and more practical, to get the mark quickly, the marks given by the teachers objective and automatic. The steps taken by the first teacher were not similar to the steps taken by the second teacher. The steps of the first teacher were (open a Gmail account , type the title of the questionnaire in the formless title , describe the purpose of making the questionnaire in the form of description section, click the purple forms icon after opening it, choose a blank worksheet, make a question on the writing on the writing of an untitled question,choose the option that has been provided by the Google Form, lock the question so turn on the option “ must be filled “ if the question must be filled, edit and format a form quiz, send questions into the Google Classroom, and the last is the result of students worksheet form’s Google Form ) while the steps of the second teacher were (open a Gmail account, choose the answer option to the right of the question, turn on the option” must be filed “if the question must be filled , choose a question options in the Google Form, give the score in the form , type the title of the questionnaire in the formless title, send questions into the classroom and the last step is open the spreadsheet to know the result of students worksheet in the Google Form) First teacher took the steps, however both of them inserted google form into Google Classroom.Keywords: Qualitative Descriptive, Google Form, Reading Descriptive Text, Junior High School.